Facilitating the co-construction of interculturality in teletandem through pedagogical mediation - Rodrigo Schaefer (DELTA: Documentação de Estudos em Lingüística Teórica e Aplicada, 2020)
ABSTRACT Telecollaboration relates to the use of online technologies in the context of language teaching and learning (O’Dowd, 2013). This study aimed at discussing how pedagogical mediation can contribute to the co-construction of interculturality in teletandem, the specific “mode of telecollaboration” (Telles, 2015a:604) in my research. Data analysis showed that opportunities for at least initial steps of a decentering attitude (Liddicoat & Scarino, 2013) came about due to pedagogical mediation, which means that teacher-mediators can encourage discussions that go beyond superficial cultural representations in the teletandem context.